2014
DOI: 10.1039/c3nj01557b
|View full text |Cite
|
Sign up to set email alerts
|

Two novel aggregation-induced emission active coumarin-based Schiff bases and their applications in cell imaging

Abstract: Two coumarin-based AIE-active compounds emitting ESIPT fluorescence with large Stocks-shifts were applied to cell imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…The applications and properties of coumarin scaffold have remarkably wide boundaries. Coumarin-based compounds have been exploited in numerous research and industrial sectors, as active pharmaceutical ingredients, pesticides, fragrances, dyes for several purposes from laser technology to organic photoredox catalysis, cell imaging, photocleavable protecting groups and fluorescent biological probes [6,[218][219][220][221][222][223][224][225]. In the following paragraphs, the most recent applications associated with the photophysical properties of coumarins have been reviewed.…”
Section: Coumarins Photopropertiesmentioning
confidence: 99%
“…The applications and properties of coumarin scaffold have remarkably wide boundaries. Coumarin-based compounds have been exploited in numerous research and industrial sectors, as active pharmaceutical ingredients, pesticides, fragrances, dyes for several purposes from laser technology to organic photoredox catalysis, cell imaging, photocleavable protecting groups and fluorescent biological probes [6,[218][219][220][221][222][223][224][225]. In the following paragraphs, the most recent applications associated with the photophysical properties of coumarins have been reviewed.…”
Section: Coumarins Photopropertiesmentioning
confidence: 99%
“…More highly efficiency, stable and multi-colored organic lightemitting materials need to be developed [2,3]. A series of aggregation induced enhanced emission (AIEE) compounds have been reported by the Tang et al [4,5], and more of these AIEE compounds have been found including styrene acrylic instead of nitrile [6,7], salicylaldehyde [8][9][10] and coumarinbased Schiff bases [11] etc. Our group has also reported AIEE compounds based on phenothiazine [12] or naphthalene [13] as the structural units.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] This approach has been successfully appliedt ot he synthesis of luminescent square tubes, [13] andt ot he detection of small amountso fhydrazine in water. [14] Salicylaldehydea zine derivatives, with AIEE properties, have also been used for cellular imaging [15,16] and as molecular probesf or the detection of thiols in live cells. [17] The study of the solid-stateo rganization of one benzophenone azine derivative providedi nsight into the importance of polymorphs,a sa changei nt he crystals tructurel ead to ac hange in the emission wavelength, induced and controlled by the application of externals timuli.…”
Section: Introductionmentioning
confidence: 99%